Viability, Information Seeking, and Vote Choice - Utych, Stephen M.; Kam, Cindy D. (The Journal of politics, 2014)
Existing research suggests that candidate viability influences strategic voting decisions among citizens. We argue that viability can influence electoral decision making beyond strategic considerations. We analyze original experimental data and novel observational data to examine viability’s impact on vote choice and information seeking. We conduct two mock primary election campaigns within the Dynamic Process Tracing Environment where we experimentally manipulate candidate viability. In both experiments, we find that subjects read more information about viable candidates, report more favorable ratings of viable candidates, and are more likely to vote for viable candidates. We demonstrate the generalizability of these results by assessing the relationship between viability, as measured with Gallup polls, and information seeking using observational data. There, we develop a unique measure of information seeking based on Google searches for the names of political candidates. These observational data reinforce the relationship between viability and information seeking.